Is quality of life reduced in people with patellofemoral osteoarthritis and does it improve with treatment? A systematic review, meta-analysis and regression. Issue 25 (4th December 2019) - Hart, Harvi F.; Filbay, Stephanie R.; Coburn, Sally; Charlton, Jesse M.; Sritharan, Prasanna; Crossley, Kay M.
Abstract: Purpose: To determine if quality of life is reduced in individuals with patellofemoral osteoarthritis, whether it can be improved with treatment, and potential factors associated with quality of life in individuals with patellofemoral osteoarthritis. Materials and methods: Published articles were identified by using electronic and manual searches. Studies reporting quality of life in individuals with patellofemoral osteoarthritis relative to a comparator group (e.g., no osteoarthritis) and intervention studies reporting quality of life in patellofemoral osteoarthritis following treatment relative to baseline/control group were included. Results: Seventeen studies (seven cross-sectional, 10 intervention) were included in this systematic review. Relative to those without osteoarthritis, individuals with patellofemoral osteoarthritis had worse knee-related quality of life (five studies) and health-related quality of life (two studies). Non-surgical treatments appear to improve knee-related quality of life compared to pre-treatment (three studies) but not control (three studies). Surgical-treatments also improved knee-related quality of life compared to pre-treatment (five studies). Worse knee-related quality of life was associated with younger age, worse pain, symptoms, function in activities of daily living, and function in sport and recreation. Conclusions: Individuals with patellofemoral osteoarthritis had worse knee-related and health-related quality of life compared to those without knee osteoarthritis. Non-surgical and surgical interventions may be effective in improving knee-related quality of life in individuals with patellofemoral osteoarthritis, but the intervention results are based on limited studies, and further research is needed to determine optimal strategies. Implications for rehabilitation: Clinicians and researchers should consider knee-related and health-related quality of life when developing treatment strategies for patellofemoral osteoarthritis. Researchers investigating the effectiveness of a treatment should compare intervention to a control group. Addressing knee pain and functional limitations may aid in improving knee-related quality of life in individuals with patellofemoral osteoarthritis.